Morphometric development of the human fetal cerebellum during the early second trimester - Xu, Feifei; Ge, Xinting; Shi, Yonggang; Zhang, Zhonghe; Tang, Yuchun; Lin, Xiangtao; Teng, Gaojun; Zang, Fengchao; Gao, Nuonan; Liu, Haihong; Toga, Arthur W.; Liu, Shuwei (NeuroImage (Orlando, Fla.), 2020)
The protracted nature of development makes the cerebellum vulnerable to a broad spectrum of pathologic conditions, especially during the early fetal period. This study aims to characterize normal cerebellar growth in human fetuses during the early second trimester. We manually segmented the fetal cerebellum using 7.0-T high-resolution MR images obtained in 35 specimens with gestational ages ranging from 15 to 22 weeks. Volume measurements and shape analysis were performed to quantitatively evaluate global and regional cerebellar growth. The absolute volume of the fetal cerebellum showed a quadratic growth with increasing gestational age, while the pattern of relative volume changes revealed that the cerebellum grew at a greater pace than the cerebrum after 17 gestational weeks. Shape analysis was used to examine the distinctive development of subregions of the cerebellum. The extreme lateral portions of both cerebellar hemispheres showed the lowest rate of growth. The anterior lobe grew faster than most of the posterior lobe. These findings expand our understanding of the early growth pattern of the human cerebellum and could be further used to assess the developmental conditions of the fetal brain. ●We manually segment the fetal cerebellum using 7.0-T MR images and specimens.●Quadratic increase of the absolute cerebellum volume.●Cerebellum with a greater pace of growth than cerebrum after 17 gestational weeks.●The extreme lateral portions of both hemispheres with the lowest rate of growth.●The anterior lobe of the cerebellum grows faster than most of the posterior lobe.